2021
DOI: 10.3390/antiox10091489
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Underlying Pulmonary Ozone Pathogenesis Regulated by Inflammatory Mediators in Mice

Abstract: Ozone (O3) is the predominant oxidant air pollutant associated with airway inflammation, lung dysfunction, and the worsening of preexisting respiratory diseases. We previously demonstrated the injurious roles of pulmonary immune receptors, tumor necrosis factor receptor (TNFR), and toll-like receptor 4, as well as a transcription factor NF-κB, in response to O3 in mice. In the current study, we profiled time-dependent and TNFR- and NF-κB-regulated lung transcriptome changes by subacute O3 to illuminate the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…WGCNA can be used to find clusters of highly correlated genes, which allows for the identification of key modules [ 24 ]. In this study, WGCNA was conducted to identify gene modules whose expression pattern was found in the in vivo pulmonary toxicity induced by different substances such as polycyclic aromatic hydrocarbons, cigarette smoke, diesel exhaust, ozone, particulate matter, bleomycin, radiation, and nanomaterials, among others ( Table S2 ) [ 10 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Once modules were identified from those publicly available transcriptomic datasets, the biological functions of each module were determined, and GSEA was conducted to ...…”
Section: Methodsmentioning
confidence: 99%
“…WGCNA can be used to find clusters of highly correlated genes, which allows for the identification of key modules [ 24 ]. In this study, WGCNA was conducted to identify gene modules whose expression pattern was found in the in vivo pulmonary toxicity induced by different substances such as polycyclic aromatic hydrocarbons, cigarette smoke, diesel exhaust, ozone, particulate matter, bleomycin, radiation, and nanomaterials, among others ( Table S2 ) [ 10 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Once modules were identified from those publicly available transcriptomic datasets, the biological functions of each module were determined, and GSEA was conducted to ...…”
Section: Methodsmentioning
confidence: 99%
“…Prior to our study, transcriptomic studies conducted in rodents identified increased expression of cholesterol biosynthesis genes in the lung beginning 12–24 hours following O 3 exposure [ 30 33 ] suggesting important roles for this pathway in O 3 responses. In the sputum samples, we observed a significant decrease in several cholesterol precursors between asthmatics and non-asthmatics ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomic and metabolomic studies have primarily identified changes in arachidonic acid metabolites and polyunsaturated fatty acids following O 3 exposure [23,26,28,29]. However, recent transcriptomic studies in rodents have identified upregulation of cholesterol biosynthesis pathway genes in the lung following O 3 exposure [30][31][32][33]. Cholesterol is the major neutral lipid component of airway surface liquid and important precursor to hormones demonstrated to modulate O 3 responses (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Vieira et al [ 24 ] report that elevated collagen levels in the lungs of OVA-challenged C57BL/6 mice were reduced by anti-TNF-α treatment. TNF-α has been found to mediate O 3 -induced lung inflammation and airway hyper-reactivity (AHR) [ 25 , 26 ], and its inhibition by adiponectin can reduce AHR [ 27 ]. It was also found that adiponectin was down-regulated in a mouse model of sensitized and challenged mice [ 28 ].…”
Section: Discussionmentioning
confidence: 99%